Young students with Down syndrome: Early longitudinal academic achievement and neuropsychological predictors. Issue 3 (2nd July 2020) - Daunhauer, Lisa A.; Will, Elizabeth; Schworer, Emily; Fidler, Deborah J.
ABSTRACT: Background: We examined longitudinal academic achievement and neuropsychological functioning across two time points in young students with Down syndrome (DS) and a typically developing (TD) comparison group equated on nonverbal mental age (NVMA). Method: Participants engaged in assessments of academic achievement, executive function (EF), and fine-motor integration. Results: From Time 1 to Time 2, students with DS demonstrated significantly more challenges than the TD group in the acquisition of quantitative skills. Additionally, EF and fine motor integration at Time 1 significantly predicted academic achievement at Time 2 for students with DS. Conclusions: The interpretation of these results extends our understanding of how early neuropsychological disruptions in DS manifest in the educational context and highlights potential targets for new interventions.